Antithrombotic drugs in acutely ill medical patients: review and meta-analysis of interventional trials with low-molecular-weight heparin and fondaparinux. (September 2013) - Loffredo, Lorenzo; Perri, Ludovica; Catasca, Elisa; Del Ben, Maria; Angelico, Francesco; Violi, Francesco
SUMMARY  Venous thromboembolism (VTE) represents a severe complication for acutely ill hospitalized medical patients. Despite several guidelines suggesting that prophylactic measures significantly reduce the risk of VTE, there is a scarce tendency to use antithrombotic drugs in these patients. We performed a meta-analysis of the interventional trials with antithrombotic drugs (low-molecular-weight heparin and fondaparinux) to oversee the clinical effectiveness and bleeding complications. A total of eight randomized controlled trials, including 16, 524 patients, were analyzed. This meta-analysis suggests that in acutely ill medical patients, compared with controls, prophylaxis with antithrombotic drugs may be of clinical benefit in VTE (odds ratio [OR]: 0.512; 95% CI: 0.41–0.64; p < 0.001) and deep venous thrombosis (OR: 0.520; 95% CI: 0.41–0.67; p < 0.001); furthermore, there is no effect on pulmonary embolism, VTE-related death and death from any other cause, and significant enhancement of hemorrhages (OR: 1.465; 95% CI: 1.2–1.79; p < 0.001). Future clinical trials should better define the risk factors for VTE in order to provide the optimal care for acutely ill medical patients.